Anaemia in systemic lupus erythematosus: from pathophysiology to clinical assessment. Issue 2 (3rd August 2005) - Giannouli, S; Voulgarelis, M; Ziakas, P D; Tzioufas, A G
Abstract : Haematological abnormalities are common in systemic lupus erythematosus. Anaemia is found in about 50% of patients, with anaemia of chronic disease being the most common form. Impaired erythropoietin response and presence of antibodies against erythropoietin may contribute to the pathogenesis of this type of anaemia. Patients with autoimmune haemolytic anaemia usually belong to a distinct category, which is associated with anticardiolipin antibodies, thrombosis, thrombocytopenia, and renal disease, often in the context of secondary antiphospholipid syndrome. Autoantibodies, T lymphocytes, and deregulation of the cytokine network can affect bone marrow erythropoiesis, leading to anaemia.